The young Nicola Pende and the ambiguous adrenal gland: at the origins of Italian endocrinology - Dibattista, Liborio (Medicina Historica, 2019)
The thesis of Niccolò Pende, supported in 1903, bore the title: The alterations of the adrenal gland after resection of the splanchnic nerve. Studies on the adrenal glands were the main gate through which the Apulian clinician became one of the first scholars in the world to attempt a systematic organization of the endocrine glands and their functions. Six years after graduating, the treatise on the physiopathology of the adrenals placed Pende on the attention not only of the Italian medical class, but also of the newly formed American magazine Endocrinology and of Sir E. Schaefer himself. The idea of ​​a close correlation between the nervous system and endocrine glands constituted the guiding idea by following which Pende built the systematic building of Italian endocrinology; however, it also constituted the limitation that prevented him - for example - from grasping the exact distinction between the functions of the cortex and medulla of the adrenal glands. The present contribution aims to underline the precisely ambiguous role that preconceived ideas play in the construction of scientific hypotheses.